The politics of nostalgia and pessimism - Adi Saleem Bharat (Francosphères)
This article provides a sociopolitical and historical analysis of Thierry Cohen’s novel Avant la haine (2015) in order to ascertain how this novel negotiates Jewish and Muslim identities and the category of ‘Jewish-Muslim relations’ and broader, more dominant representations of these identities and relations. In doing so, I show how literary interventions into the question of Jewish-Muslim relations and their representations may both challenge and reaffirm polarizing discourses of Jewish-Muslim tension more broadly found in contemporary French society. Most significantly, this novel is steeped in pessimism or at the very least a pessimistic optimism when it comes to perceiving Jewish-Muslim presents and futures. This sense of pessimism suggests the difficulty of articulating counter-narratives in a contemporary context that consistently emphasizes Jewish-Muslim polarization, overdetermined by theories of a new Muslim antisemitism and an importation of the Israeli-Palestinian conflict. This article’s conclusions are not meant to apply to all literary productions on Jewish-Muslim (or inter-ethnic/-religious) relations, but rather to be exploratory in nature, i.e. to suggest how literature may mediate and navigate intergroup relations that are presented as polarized and tense in broader media and political discourses.